2020
DOI: 10.2147/ijwr.s252934
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sicilian Wine’s Effect on Consumers’ Identity-Behavioral Intentions: The Mediation Effect of Subjective Norms and Social Activity</p>

Abstract: Wine has a purely symbolic connotation in the eyes of consumers and the market. Therefore, it could lead to a different consideration and perception of buying local wine which could be sensed as a social experience rather than an automatic action. The research aim is to highlight the bond between customers and the product (Sicilian DOC wine) by overcoming the utilitarian limit and showing the social one. This study has the purpose of understanding in depth how individual behavior and social relationships are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 32 publications
(36 reference statements)
1
6
0
8
Order By: Relevance
“…Subjective norms has also turned out to be a factor that has an influence on local wine consumption intention, coinciding with the findings of the majority of studies that looked into this dimension, such as the work of Capitello et al [30]; St James and Christodoulidou [50], Thompson and Vourvachis [51], van Zanten [52] and Scuderi et al [26].…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Subjective norms has also turned out to be a factor that has an influence on local wine consumption intention, coinciding with the findings of the majority of studies that looked into this dimension, such as the work of Capitello et al [30]; St James and Christodoulidou [50], Thompson and Vourvachis [51], van Zanten [52] and Scuderi et al [26].…”
Section: Discussionsupporting
confidence: 60%
“…In a context related to the purchase of local foods, Shin and Hancer [ 14 ] confirmed how subjective norms are significant predictors of the formation of attitudes towards them, which in turn have an indirect influence on intention to buy. Furthermore, Scuderi et al [ 26 ] studied intention to buy wine on the island of Sicily and confirmed that subjective norms correlate positively with perceived behavioural control. Therefore, in this study on local wine, it is proposed that there is an indirect relationship between subjective norms and local wine consumption intention through attitude towards them and perceived behavioural control.…”
Section: Methodsmentioning
confidence: 89%
See 3 more Smart Citations